Need to clamp indwelling urinary catheters before removal after different durations: a systematic review and meta-analysis - Xiaoyan Fan; Sumin Ma; Jiayi Gu (BMJ Open)
Objective This meta-analysis aimed to evaluate the effect of bladder training by clamping on bladder urethral function in patients with indwelling urinary catheters used for different durations.Design Systematic review and meta-analysis.Data sources The UpToDate, Cochrane Library, OVID, PubMed, China National Knowledge Infrastructure, CINAHL and Embase were screened from 1 January 2000 to 28 February 2022.Eligibility criteria for selecting studies Randomised controlled trials (RCTs) or quasi-experimental designs comparing the efficacy of bladder training in patients with an indwelling urinary catheter by clamping or free drainage before urinary catheter removal were published in English or Chinese.Data extraction and synthesis Two reviewers independently extracted the data and assessed the quality of studies. Continuous variables were analysed using mean difference and standardised mean difference (SMD) values with a 95% CI. Categorical variables were analysed using relative risk (RR) and 95% CI.Primary and secondary outcome measures The primary outcome was urinary tract infection incidence, and secondary outcomes included hours to first voiding, incidence of urinary retention and recatheterisation and residual urine volume.Results Seventeen papers (15 RCTs and 2 quasi-RCTs) comprising 3908 participants were included in the meta-analysis. The pooled results of the meta-analysis showed that the clamping group had a significantly higher risk of urinary tract infections (RR=1.47; 95% CI 1.26 to 1.72; p<0.00001) and a longer hour to first void (SMD=0.19; 95% CI 0.08 to 0.29; p=0.0004) compared with the free drainage group. Subgroup analysis of indwelling urinary catheter use durations of ≤7 days indicated that clamping significantly increased the risk of urinary tract infection (RR=1.69; 95% CI 1.42 to 2.02, p<0.00001) and lengthens the interval to first void (SMD=0.26, 95% CI 0.11 to 0.41, p=0.0008) compared with free drainage.Conclusions Bladder training by clamping indwelling urinary catheters increases the incidence of urinary tract infection and lengthens the hours to first void in patients with indwelling urinary catheters use durations of ≤7 days compared with the free drainage. However, the effect of clamping training on patients with an indwelling urinary catheter use duration of >7 days is unclear.